Exploring Associate English Teachers’ Early Career Path Experiences in Private Schools - Shahbazli, Sevinj; Mammadzada, Narmin; Jafarova, Reyhan; Asgarli, Nigar (ADA University, 2024)
This study investigated the professional development experiences of Associate English teachers at private schools in Baku, Azerbaijan. The study employed qualitative interviews with both associate teachers (nine) and school administrators (two) selected through purposive sampling, particularly applying a homogeneous sampling strategy, which provided insights into the perspectives of professional growth possibilities, issues encountered, and support systems accessible. The data analyzed were sorted, organized, and then coded. Finally, labeling was applied to identify basic and global themes. The responses of interviewed Associate English teachers and school principals were triangulated to facilitate the validation of the data. The research findings were verified accurately through member checking to avoid misunderstanding in respondents' answers and to uncover Capstone Project team members’ biases and misconceptions. Throughout the study, the participants were treated respectfully, and their rights were protected via a consent form. The participants’ anonymity was secured, they were given pseudonyms, and their responses were not shared and discussed with others. Also, audio recordings, transcripts of interviews, consent forms, and were saved in one of the team members’ laptops and deleted later. The findings shed light on a multidimensional context in which Associate English teachers placed a high value on ongoing learning and cooperation. Challenges such as adjusting to new surroundings, communication challenges, and restricted internal advancement prospects appeared to be important impediments, emphasizing the importance of resilience-building measures. Support from colleagues and formal professional development activities were appreciated, emphasizing the necessity of cultivating a supportive school culture. Furthermore, suggestions for development included creating transparent professional growth paths, increasing participation in international seminars, and cultivating a collaborative environment. Finally, the study emphasized the importance of strong support systems in enabling Associate English teachers to effectively navigate the complexities of the profession and thrive in their roles, ensuring the long-term viability of the teaching profession in Baku's private school settings. As a final product, the Capstone Project team devised a guidebook titled ‘Steps Leading to Success in Professional Development for Associate English Teachers in Private Schools.’
Keywords: Teacher professional development; Private schools -- Azerbaijan; Teacher training -- Challenges -- Azerbaijan; Career development -- Teachers -- Professional support systems; Azerbaijan -- Education -- Teacher training; Education